Level of Adherence and Associated Factors Among HIV-Infected Patients on Antiretroviral Therapy in Northern Ethiopia: Retrospective Analysis - Desta AA; Kidane KM; Woldegebriel AG; Ajemu KF; Berhe AA; Zgita DN; Teweldemedhn LW; Woldegebriel LL; Bezabih NM; Woldearegay TW (Patient Preference and Adherence, 2020)
Abraham Aregay Desta, Kibriti Mehari Kidane, Ataklti Gebretsadik Woldegebriel, Kiros Fenta Ajemu, Asfawosen Aregay Berhe, Degnesh Negash Zgita, Letebrhan Weldemhret Teweldemedhn, Lemlem Legesse Woldegebriel, Nega Mamo Bezabih, Tewolde Wubayehu Woldearegay Tigray Health Research Institute, Mekelle, Tigray, EthiopiaCorrespondence: Abraham Aregay Desta Email abaregaydesta@gmail.comBackground: Poor adherence to ART increases viremia, which leads to disease progression and transmission of drug-resistant HIV strains. This study aimed to assess the level of ART adherence and associated factors among adolescents and adult patients enrolled in ART care in Northern Ethiopia.Methods: A retrospective analysis was conducted among 19,525 patients from April 2015 to March 2019. Data verification and filtration were done in Excel 2013 before exporting to STATA 14.0. Ordinal logistic regression was used to analyze the data.Results: About 94.84%, 95% CI (94.52%, 95.14%) of the study subjects were in good adherence. However, about 1.46%, 95% CI (1.30%, 1.64%) and 3.70%, 95% CI (3.44%, 3.97%) of them had poor and fair adherence respectively. In the adjusted analysis, being male (AOR =  0.75; 95% CI: 0.0.65, 0.87), patients from general hospitals (AOR =  0.52; 95% CI: 0.39, 0.69), WHO staging IV (AOR = 0.57; 95% CI: 0.41, 0.81) and non-suppressed viral load (VL) status (AOR = 0.54; 95% CI: 0.47, 0.63) were negatively associated with good adherence. Whereas, age of 50+ years old (AOR =  1.68; 95% CI: 1.13, 2.50), recent CD4 count of 200– 499 (AOR = 1.45; 95% CI: 1.21, 1.74) and recent CD4 count of 500 and above (AOR = 1.84; 95% CI: 1.47, 2.32) were positively associated with good ART drug adherence.Conclusion: There was a higher level of adherence compared to the previous studies conducted in Ethiopia. Being male, patients from general hospitals, WHO staging II, II and IV and non-suppressed VL status were negatively associated with good adherence. Whereas, older ages, recent CD4 count of 200– 499 and ≥ 500 CD4 count were positively associated with good ART drug adherence. The health system should recognize a higher need of younger age groups and males to design targeted counseling and support to encourage consistently high levels of adherence for a better ART treatment outcome.Keywords: adherence and compliance, antiretroviral therapy, retreatment